Tropical forest greenhouse gas emissions: root regulation of soil processes and fluxes - Girkin, Nicholas T. (2018)
Tropical forested peatlands are a major carbon store and are a significant source of global carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O) emissions. While the role of environmental variables, including temperature and water table depth have been relatively well studied, uncertainty remains in the extent to which plant roots regulate greenhouse gas (GHG) fluxes and peat biogeochemistry. This study examined the role of roots, and root inputs of carbon and oxygen in regulating fluxes from peat under two dominant plant species, Campnosperma panamensis and Raphia taedigera, a broadleaved evergreen tree and canopy palm, in San San Pond Sak wetland, in Bocas del Toro Province, Panama. A combination of in situ and ex situ experiments were performed between February 2015 and August 2017. Small scale variation in GHG fluxes and peat biogeochemistry was measured at two distances within the rooting zones of C. panamensis and R. taedigera. Peat organic matter properties were assessed using Rock-Eval 6 pyrolysis. Results indicated significant variation in CH4 but not CO2 fluxes at different distances within the rooting zone, with CH4 fluxes subsequently linked to measures of the overall size of the available organic carbon pool (S2). Rock-Eval pyrolysis data was used to construct a three-pool model of organic matter thermostability which indicated significant differences in organic matter composition between peats derived from different botanical origins, in addition to a high level of heterogeneity within the rooting zone. Changes in GHG production and peat biogeochemical properties in response to the addition of root exudate analogues were assessed in an ex situ anoxic incubation experiment. A combination of organic acids and sugars, identified as common forest plant root exudate components, were added over a two week period to peats derived from C. panamensis and R. taedigera. GHG fluxes varied significantly between treatments but not by peat botanical origin, and were associated with significant changes in soil properties including, pH and redox potential, thereby demonstrating a link between plant root carbon inputs, peat properties and GHG fluxes. In situ mesocosms were used to assess the effects of root exclusion on peat biogeochemistry and GHG fluxes. Partial and full root exclusion significantly reduced dissolved oxygen concentrations and was associated with greater root necromass. Full root exclusion increased CH4 fluxes five-six fold compared to partial root exclusion, equivalent to an 86 – 90% reduction in CH4 oxidation, demonstrating the important role of root inputs of oxygen in mitigating CH4 efflux from tropical peat. A 13CO2 pulse labelling experiment was conducted using both R. taedigera, C. panamensis, and Symphonia globulifera, a second broadleaved evergreen tree species, to demonstrate a direct link between plant photosynthesis and CH4 fluxes, and identify aspects of the bacterial and fungal community associated with the turnover of labile carbon. The extent of 13C enrichment of CH4 differed significantly between plant types (palms vs broadleaved evergreen trees), as did the extent of net CH4 efflux. Phospholipid fatty acid (PLFA) biomarker analysis indicated both peat types were dominated by Gram negative bacteria. There was strong 13C enrichment of Gram negative bacteria, supporting their previously proposed role as important decomposers of labile carbon. Collectively, these results demonstrate that root inputs of carbon and oxygen can strongly regulate tropical peatland GHG fluxes, and that the extent of regulation can vary significantly between tropical wetland plant species from contrasting dominant plant types. This is particularly important in understanding regulatory processes in a globally significant carbon store and understanding possible consequences of land use change in the tropics.